La Contrattazione colletiva in Italia (1945-1977) ; Democrazia politica e democrazia industriale - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "La Contrattazione colletiva in Italia (1945-1977)," by Bruno Veneziani, Edited. This article reviews the book, "Democrazia politica e democrazia industriale," by Silvana Sciarra.